2021
DOI: 10.1007/s00535-021-01798-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical costs according to the stages of colorectal cancer: an analysis of health insurance claims in Hachioji, Japan

Abstract: Background Although the effect of the early detection of colorectal cancer (CRC) on medical costs needs to be clarified, there are few reports on the actual medical costs of CRC patients in Japan. We aimed to identify medical costs according to CRC stage, using health insurance claims. Methods This observational study included CRC patients who had received specific treatment for CRC, which was defined by the procedure code and the claim computer processing system code associated with the treatment of CRC. CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…Studies varied in countries where they were conducted, which included the USA [ 11 , 17 , 19 ], England [ 15 , 18 ], France [ 16 ], China [ 12 , 20 ], Korea [ 10 ], Vietnam [ 13 ], Italy [ 14 ], Australia [ 21 ], Canada [ 22 ] and Japan [ 23 ]. Five studies utilized claims data from a health insurance database [ 10 , 16 , 17 , 19 , 23 ], three used data abstracted from hospital medical records [ 12 , 13 , 20 ], four used administrative health data [ 14 , 15 , 18 , 22 ], one study used data from a nationally representative medical expenditure survey [ 11 ], lastly another study linked self-reported survey data with an administrative health database [ 21 ]. It must also be noted that studies which relied on either survey data [ 11 , 21 ] or hospital medical records [ 12 , 13 , 20 ], may omit data from non-responders and those receiving care from other hospital(s), respectively, which may impact the generalizability of their cost estimates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies varied in countries where they were conducted, which included the USA [ 11 , 17 , 19 ], England [ 15 , 18 ], France [ 16 ], China [ 12 , 20 ], Korea [ 10 ], Vietnam [ 13 ], Italy [ 14 ], Australia [ 21 ], Canada [ 22 ] and Japan [ 23 ]. Five studies utilized claims data from a health insurance database [ 10 , 16 , 17 , 19 , 23 ], three used data abstracted from hospital medical records [ 12 , 13 , 20 ], four used administrative health data [ 14 , 15 , 18 , 22 ], one study used data from a nationally representative medical expenditure survey [ 11 ], lastly another study linked self-reported survey data with an administrative health database [ 21 ]. It must also be noted that studies which relied on either survey data [ 11 , 21 ] or hospital medical records [ 12 , 13 , 20 ], may omit data from non-responders and those receiving care from other hospital(s), respectively, which may impact the generalizability of their cost estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, studies by Gigli and Taplin et al, focused on rectal [ 14 ] and colon [ 17 ] cancer, respectively, while Goldsbury et al, stratified cost estimates by age and cancer site (i.e., colon and rectum) [ 21 ]. CRC was identified using International Disease Classification codes in 10 studies [ 10 , 13 , 14 , 16 – 19 , 21 – 23 ], two studies used hospital medical records [ 15 , 20 ], and two studies relied on self-reported diagnosis [ 11 , 12 ]. With respect to cancer stage at diagnosis, 10 studies included CRC patients with stage I to IV disease [ 12 – 18 , 20 , 22 , 23 ], two studies did not report cancer stage [ 10 , 11 ], one study included CRC patients with a stage IV de novo (no prior CRC diagnosis) diagnosis or a recurrent (previously diagnosed with stage I-III CRC) cancer diagnosis [ 19 ], and one study reported cancer severity by the extent of cancer metastasis (i.e., localized, regional, distant metastases) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations